2005
DOI: 10.1128/aem.71.1.227-239.2005
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Environmental Sources of Variation in Lake Bacterial Community Composition

Abstract: This study used a genetic fingerprinting technique (automated ribosomal intergenic spacer analysis[ARISA]) to characterize microbial communities from a culture-independent perspective and to identify those environmental factors that influence the diversity of bacterial assemblages in Wisconsin lakes. The relationships between bacterial community composition and 11 environmental variables for a suite of 30 lakes from northern and southern Wisconsin were explored by canonical correspondence analysis (CCA). In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
259
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(289 citation statements)
references
References 81 publications
16
259
4
4
Order By: Relevance
“…The influence of both factors at intermediate scales was already shown by other studies (Green et al, 2004;Reche et al, 2005;Yannarell and Triplett, 2005), but our study suggest an effect of both factors for large scales as well, as shown for soil microbial communities (Fierer and Jackson, 2006). Although the small size, high dispersal rates, large population size and low extinction rates of microorganisms suggest a low effect of geographic barriers on microorganisms (Staley and Gosink, 1999;Beja et al, 2002;Finlay, 2002;Ramette and Tiedje, 2007), our study shows that the distribution of microorganisms in deep-sea sediments is limited at intermediate (10-3000 km) and large scales (43000 km).…”
Section: Diversity and Biogeography In Deep-sea Sediments R Schauer Esupporting
confidence: 51%
“…The influence of both factors at intermediate scales was already shown by other studies (Green et al, 2004;Reche et al, 2005;Yannarell and Triplett, 2005), but our study suggest an effect of both factors for large scales as well, as shown for soil microbial communities (Fierer and Jackson, 2006). Although the small size, high dispersal rates, large population size and low extinction rates of microorganisms suggest a low effect of geographic barriers on microorganisms (Staley and Gosink, 1999;Beja et al, 2002;Finlay, 2002;Ramette and Tiedje, 2007), our study shows that the distribution of microorganisms in deep-sea sediments is limited at intermediate (10-3000 km) and large scales (43000 km).…”
Section: Diversity and Biogeography In Deep-sea Sediments R Schauer Esupporting
confidence: 51%
“…Approximately 0.1% of the microbiome sequences had significant similarity (Eo0.001) to 16S rDNA genes in the Ribosomal Database Project (Cole et al, 2007). On the basis of these similarities, the microbial communities in the freshwater ponds exhibited typical freshwater bacterial groups as previously seen in other 16S rDNA surveys of freshwater environments (Arias et al, 2004;Lindstrom et al, 2005;Yannarell and Triplett, 2005;Briee et al, 2007). Corresponding analyses of microbiomes from the solar salterns showed the expected shift to an Archaea-dominated community in the high salinity pond (RodriguezValera et al, 1985;Benlloch et al, 2002).…”
Section: Resultsmentioning
confidence: 59%
“…Ramette (2007) suggested that these tools can also be readily applied in microbial ecology to help reduce data set complexity as DNA sequence data are increasingly available because of high-throughput sequencing technologies. Indeed, microbial ecology studies have increasingly used multivariate analyses to relate environmental variation with bacterial composition in aquatic systems (Yannarell and Triplett, 2005;Kent et al, 2007;Rubin and Leff, 2007), to determine bacterial community dynamics in relation to temporal variation in marine ecosystems (Pringault et al, 2007;Sapp et al, 2007), to develop microbial communities as indicators of ecosystem stress Córdova-Kreylos et al, 2006;Fields et al, 2006), as well as to link geophysical signatures to microbial communities (Allen et al, 2007).…”
Section: Engineering Controlsmentioning
confidence: 99%